2014
DOI: 10.1007/s11010-014-2241-x
|View full text |Cite
|
Sign up to set email alerts
|

LAP1 is a crucial protein for the maintenance of the nuclear envelope structure and cell cycle progression

Abstract: Cell division in eukaryotes requires the disassembly of the nuclear envelope (NE) at the beginning of mitosis and its reassembly at the end of mitosis. These processes are complex and involve coordinated steps where NE proteins have a crucial role. Lamina-associated polypeptide 1 (LAP1) is an inner nuclear membrane protein that has been associated with cell cycle events. In support of this role, LAP1 has been implicated in the regulation of the NE reassembly and assembly of the mitotic spindle during mitosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
3
29
0
Order By: Relevance
“…During prometaphase (NE disassembly), LAP1 seems to redistribute throughout the endoplasmic reticulum (ER), and lose its association to chromosomes and lamins, thus contributing to the NE breakdown [6,7,19,22]. Recently it was shown that, during the cell cycle, LAP1 plays a role in centrosome distancing from the nuclear envelope [23]. This reinforces a role for LAP1 as a key player participating in NE structural maintenance, during progression of the cell cycle.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…During prometaphase (NE disassembly), LAP1 seems to redistribute throughout the endoplasmic reticulum (ER), and lose its association to chromosomes and lamins, thus contributing to the NE breakdown [6,7,19,22]. Recently it was shown that, during the cell cycle, LAP1 plays a role in centrosome distancing from the nuclear envelope [23]. This reinforces a role for LAP1 as a key player participating in NE structural maintenance, during progression of the cell cycle.…”
Section: Introductionmentioning
confidence: 93%
“…This reinforces a role for LAP1 as a key player participating in NE structural maintenance, during progression of the cell cycle. It is particularly noteworthy that LAP1 knockdown resulted in a decrease of mitotic cells and reduced levels of a-tubulin acetylated and lamin B1 [23]. LAP1 is highly phosphorylated during mitosis.…”
Section: Introductionmentioning
confidence: 97%
“…However, despite being one of the first LAPs identified [13], the physiological functions of this ubiquitously-expressed NE protein remain poorly understood. Nevertheless, LAP1 has been implicated in the regulation of the NE structure, cell cycle progression, mitosis, NE localization of torsinA and regulation of its ATPase activity, as well as skeletal muscle maintenance [14,15,16]. In our previous work, LAP1 was found in the mitotic spindle, mid-body and centrosomes, indicating a strong functional association between LAP1 and these cell cycle-related components.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, LAP1 colocalizes with γ-tubulin in centrosomes at metaphase and anaphase during mitosis. In addition, LAP1 depletion seems to be correlated with altered centrosome positioning and a decrease in the number of mitotic cells [15]. LAP1 association with cell cycle progression is particularly interesting as it shares functional elements with spermatogenesis, in particular with meiosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation